A Pan-Cancer Analysis of Natriuretic Peptide Receptor 3 (NPR3) with Clinical Cohort and in vitro Validation - Liu Y; Liu J; Li Y; Zhao Z; Lyu D; Dong K; Wei M; Huang R; Lu B; Pan X (Journal of Inflammation Research)
Yifan Liu,1,* Jiangui Liu,1,* Yuanan Li,1,* Zihui Zhao,1,* Donghao Lyu,1 Keqin Dong,1 Maodong Wei,1 Runzhi Huang,2 Bingnan Lu,1 Xiuwu Pan1 1Department of Urology, Xinhua Hospital Affiliated to Shanghai Jiao Tong University School of Medicine, Shanghai, 200092, People’s Republic of China; 2Department of Burn Surgery, the First Affiliated Hospital of Naval Medical University, Shanghai, 200433, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiuwu Pan, Department of Urology, Xinhua Hospital Affiliated to Shanghai Jiao Tong University School of Medicine, No. 1665 Kongjiang Road, Shanghai, 200092, People’s Republic of China, Email panxiuwu@126.com Bingnan Lu, Department of Urology, Xinhua Hospital Affiliated to Shanghai Jiao Tong University School of Medicine, No. 1665 Kongjiang Road, Shanghai, 200092, People’s Republic of China, Email 972081060@qq.comBackground: Natriuretic peptide receptor 3 (NPR3) regulates natriuretic peptides and plays a key role in angiogenesis, immune regulation, and progression of certain cancers. However, the clinical significance of NPR3 at pan-cancer level remains poorly understood. This study aimed to comprehensively analyze NPR3’s role across multiple cancers, focusing on its potential as a prognostic biomarker, particularly in kidney cancer.Methods: A comprehensive pan-cancer study of NPR3 was conducted using 20 different databases and datasets. The study included differential expression analysis, competing endogenous RNA (ceRNA) analysis, protein–protein interaction (PPI) analysis, Kaplan–Meier (K-M) survival analysis, and correlation assessments of NPR3 with clinical characteristics, tumor purity, tumor genomics, tumor immunity, drug sensitivity, molecular docking, and signaling pathways. Additionally, using a cohort of 370 patients diagnosed with kidney neoplasms, immunohistochemistry (IHC) was employed to assess NPR3 expression differences between tumor and normal tissues. The IHC cutoff point was determined using the “surv_cutpoint” function, followed by survival analysis. Multiple external datasets were used to validate the results. Cell-based experiments in 786-O, 769-P, and A-498 cell lines were further conducted.Results: In pan-cancer, NPR3 was down-regulated in most of the tumor types, and ceRNA and PPI network were constructed. Moreover, NPR3 expression was significantly associated with the clinical prognosis and stages, tumor purity, genetic mutation, immune infiltration and signaling pathways and drug sensitivity. In kidney neoplasm, NPR3 was down-regulated, and higher expression was associated with a better prognosis. Multivariate Cox regression analysis showed that NPR3 expression was protective factor for both OS (HR = 0.50, 95% CI = 0.29– 0.87, p = 0.013) and PFS (HR = 0.66, 95% CI = 0.46– 0.95, p = 0.024). In renal cancer cells, NPR3-knockdown significantly suppressed tumor proliferative and migration activity.Conclusion: NPR3 servers as a prognostic and immunotherapeutic biomarker in pan-cancer, but its biological role and potential as a therapeutic target warrants further investigation.Keywords: NPR3, pan-cancer, kidney cancer